Kaempferia sipraiana (Zingiberaceae), a new species from Thailand and a new record of Kaempferia pseudoparviflora for Myanmar - THAWATPHONG BOONMA; SURAPON SAENSOUK; PIYAPORN SAENSOUK (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Boonma T, Saensouk S, Saensouk P. 2022. Kaempferia sipraiana (Zingiberaceae), a new species from Thailand and a new record of Kaempferia pseudoparviflora for Myanmar. Biodiversitas 23: 2203-2211. Kaempferia sipraiana Boonma & Saensouk, a new species of Kaempferia subgenus Protanthium (Zingiberaceae) from northern Thailand and K. pseudoparviflora Saensouk P. & Saensouk, a new record species of Kaempferia subgenus Kaempferia for Myanmar are described, illustrated, and photographed. The dominant characters of Kaempferia sipraiana were leaves narrowly elliptic, green with short white stripes arranged parallel along the leaf edges, between the midrib and both sides of the edges, apex acuminate with slightly mucronate, base attenuate-oblique; peduncle glabrous; bracts apex mucronate, glabrous, red with dark red veins; bracteoles glabrous; floral tube shorter than calyx; calyx glabrous; staminodes oblanceolate, apex 3-lobes like curly brackets; labellum white at the base with pinkish purple in the middle gradually fade to pale pink and to reach to white tip and edge respectively, apex 3-lobes like curly brackets, each lobe 3.0–3.3 cm long; apex 4 lobes, outer lobes acute, inner lobes obtuse rarely combined to truncate; stigma with pink lips. The dominant characters of K. pseudoparviflora were one leaf and dark green with light grey markings, the inflorescence looks like inflorescence of K. parviflora. The information on vernacular name, distribution, phenology, ecology, conservation status, specimens examined, and an identification key to both species of Kaempferia in Thailand is revised and presented.